The Prognostic Value of C-Reactive Protein Levels in Patients with Community Acquired Pneumonia (Medical Forum Monthly, 2025)
Objective: To determine the predictive accuracy of C-reactive protein levels in patients with community-acquired pneumonia in predicting the complications of pneumonia.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Pediatric medical unit of The Children’s Hospital & UCHS Lahore from 05 December 2024 to 05 May 2025.Methods: Non-Probability Consecutive Sampling technique used. The calculated with 95% confidence level with 7% margin of error and 80% magnitude 115 cases. A total of 115 children fulfilling the selection criteria were enrolled after taking written informed consent from parents. Clinical proforma was used to record data of the patients, e.g. demographic profile, C-reactive protein value at admission and on day 4, fever, cough, tachypnea, wheezing etc. The outcomes of interest were assessed as: 7-day mortality; need for mechanical ventilation and/or inotropic support; development of complicated pneumonia.Results: Of these 115 study cases, 78(67.8%) were male patients, while 37(32.2%) were female patients. Mean age of our study cases was 27.65±14.68 months. Of these 115 study cases, 95(82.6%) were vaccinated and 20(17.4%) were un-vaccinated. Mean CRP level in our study was 8.23±6.12 mg/L and it was raised (>10mg/L) in 53(46.1%). Complications were noted in 37(32.2%), while sensitivity, specificity, PPV, NPV and diagnostic accuracy was 83.8%, 71.8%, 58.5%, 90.3% and 75.7%, respectively.Conclusion: Our study results support use of serum CRP levels in children presenting with severe pneumonia as it was found to be highly sensitive, specific, high positive predictive value & negative predictive value and highdiagnostic accuracy. All clinicians treating such patients can employ serum CRP levels for early diagnosis followed by timely management achieve desired outcomes.